Effect and safety of drospirenone and ethinylestradiol tablets (II) for dysmenorrhea: A systematic review and meta-analysis - Shi, Jinghua; Leng, Jinhua (Frontiers in Medicine, 2022)
Aim: This systematic review aimed to assess the efficacy and safety of Drospirenone and Ethinylestradiol Tablets (Ⅱ) in the treatment of dysmenorrhea. Methods: Mainstream electronic databases were searched. Both randomized controlled trials (RCTs) and non-randomized studies were included. Meta-analyses were performed. Results: A total of 11 studies involving 2251 participants with dysmenorrhea were included. When Drospirenone and Ethinylestradiol Tablets (Ⅱ) conventional 24/4-day regimen was compared with placebo, the total efficiency rate (defined as pain symptom disappeared or relieved) in Drospirenone and Ethinylestradiol Tablets (Ⅱ) 24/4-day regimen group was higher than in placebo group (RR=5.55, 95%CI: 2.48 to 12.39, P< 0.0001). No clear differences were found on risk of overall adverse events or specific adverse events. When Drospirenone and Ethinylestradiol Tablets (Ⅱ) was compared with active control drugs, no clear differences were found on the total efficiency rate, visual analog scale (VAS) scores for dysmenorrhea and other related pain. The risk of overall adverse events decreased in Drospirenone and Ethinylestradiol Tablets (Ⅱ) conventional 24/4-day regimen (13/53 versus 66/148, RR=0.55, 95%CI: 0.33 to 0.91) when compared with active control drugs group. When Drospirenone and Ethinylestradiol Tablets (Ⅱ) flexible extended regimen was compared with conventional 24/4-day regimen, the number of days of dysmenorrhea (MD=−3.98, 95%CI: −5.69 to −2.27), and dysmenorrhea associated with unscheduled bleedings (MD=−1.6, 95%CI: −2.8 to −0.5) were fewer in flexible extended regimen. Conclusions: The Drospirenone and Ethinylestradiol Tablets (Ⅱ) could improve symptoms of dysmenorrhea and decrease other related pain symptoms, improve quality of life. More high-quality evidence is needed to confirm the advantages.